2019
DOI: 10.5194/isprs-archives-xlii-4-w12-127-2019
|View full text |Cite
|
Sign up to set email alerts
|

Fusing of Optical and Synthetic Aperture Radar (Sar) Remote Sensing Data: A Systematic Literature Review (Slr)

Abstract: <p><strong>Abstract.</strong> Remote sensing and image fusion have recognized many important improvements throughout the recent years, especially fusion of optical and synthetic aperture radar (SAR), there are so many published papers that worked on fusing optical and SAR data which used in many application fields in remote sensing such as Land use Mapping and monitoring. The goal of this survey paper is to summarize and synthesize the published articles from 2013 to 2018 which focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A vast number of studies have used the fusing of various sources of RS data for different aspects of land use and land cover classification [27,28]. In an analysis including 32 studies reviewing the advantages of fusing optical and radar data for land use analysis, the vast majority concluded that the fusion of RS data improved forest classification compared to using a single source [29].…”
Section: Introductionmentioning
confidence: 99%
“…A vast number of studies have used the fusing of various sources of RS data for different aspects of land use and land cover classification [27,28]. In an analysis including 32 studies reviewing the advantages of fusing optical and radar data for land use analysis, the vast majority concluded that the fusion of RS data improved forest classification compared to using a single source [29].…”
Section: Introductionmentioning
confidence: 99%
“…We can make a direct comparison with the stacking technique, a popular way of pixel-level fusing data from different sensors [20]. Direct stacking of bands can be used to derive ζ (without the Kronecker product).…”
Section: B Experiments -Ii: Dual-pol Sar -Multi-spectral Modalitymentioning
confidence: 99%
“…Multi-modal data includes, but is not limited to, dual-frequency polarimetric SAR (or PolSAR) or SAR-MS images from sensors with different spectral channels and resolutions. Various techniques for the fusion of SARoptical and subsequent CD algorithms have been reported in [20].…”
Section: Introductionmentioning
confidence: 99%
“…The three most commonly used Optical-Radar fusion methods at pixel level are Principal Component Analysis (PCA) [11], intensity-hue-saturation (IHS) [12], and discrete wavelet transform [13]. According to previous studies, PCA is the most preferred method of the three methods [14], while the Minimum Noise Fraction (MNF) transformation performs two separate standard PCA transformation of the noise-whitened data [15], and also aims to produce principal components by maximizing the signal-to-noise ratio of the data [16].…”
Section: Introductionmentioning
confidence: 99%